2022
DOI: 10.1200/jco.2022.40.17_suppl.lba501
|View full text |Cite
|
Sign up to set email alerts
|

LUMINA: A prospective trial omitting radiotherapy (RT) following breast conserving surgery (BCS) in T1N0 luminal A breast cancer (BC).

Abstract: LBA501 Background: Adjuvant breast RT is usually prescribed following BCS to reduce the risk of local recurrence (LR). However, this treatment is inconvenient, costly, and associated with acute and late toxicity. Traditional clinical pathological factors (CPFs) alone are limited in their ability to identify women with a low enough risk of LR to omit RT. Molecular defined intrinsic subtypes of BC provide additional prognostic information with luminal A having the lowest risk of recurrence. A retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 0 publications
0
48
1
2
Order By: Relevance
“…Recently, the LUMINA trial, a prospective multicenter cohort study, also showed that endocrine therapy alone achieved very low rates of local recurrence without postoperative irradiation (5-year rate, 2.3%) in patients 55 years or older affected by a luminal-like, grade 1-2, pT1 N0 breast cancer. 27 However, it should be strongly considered that adjuvant endocrine therapy might significantly compromise patients' HRQoL. 28 Moreover, compliance and adherence to planned endocrine therapy are well known to decrease over time.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, the LUMINA trial, a prospective multicenter cohort study, also showed that endocrine therapy alone achieved very low rates of local recurrence without postoperative irradiation (5-year rate, 2.3%) in patients 55 years or older affected by a luminal-like, grade 1-2, pT1 N0 breast cancer. 27 However, it should be strongly considered that adjuvant endocrine therapy might significantly compromise patients' HRQoL. 28 Moreover, compliance and adherence to planned endocrine therapy are well known to decrease over time.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…LUMINA trial is a phase III study of 500 patients 55 years or older with invasive ductal cancer stage I HR-positive, luminal A, defined as ER≥1%, PR >20 %, HER2-negative and Ki 67 ≤13.25%, grade 1 or 2, omitting radiation therapy after lumpectomy, sentinel node biopsy and endocrine therapy. The study is reporting a 5 year follow up a with a 2.3% local recurrence rate, concluding that patients with low-risk breast cancer can forgo radiation therapy after breast conserving surgery and endocrine therapy (47). Can we now omit radiation therapy?…”
Section: Early-stage Hr-positive Breast Cancermentioning
confidence: 99%
“…Abstract Chmura 2 Oral 1007 Breast LUMINA: A prospective trial omitting radiotherapy (RT) following breast conserving surgery (BCS) in T 1 N 0 luminal A breast cancer (BC). Abstract 363918 Whelan 5 Oral LBA501 CNS Phase II randomized study comparing proton craniospinal irradiation with photon involved-field radiotherapy for patients with solid tumor leptomeningeal metastasis Yang 10 Oral 2000 CNS A controlled comparison of cerebral volume loss after brain irradiation with proton versus photon radiotherapy. Abstract 376740 Gardner 12 Poster discussion 2017 GI Single agent PD-1 blockade as curative-intent treatment in mismatch repair deficient locally advanced rectal cancer.…”
Section: Introductionmentioning
confidence: 99%